Ruxolitinib for myelofibrosis - GU, LIAN (D.A. Spandidos, 2013)
The aim of the present study was to assess the beneficial and harmful effects of ruxolitinib in patients with myelofibrosis (MF). The Cochrane databases, PubMed and Embase were searched for studies published up to October 2012. Randomised controlled trials assessing ruxolitinib versus a placebo or the best available therapy in patients with MF were included. Two trials randomised 528 patients with MF to ruxolitinib versus a placebo or ruxolitinib versus the best available therapy. Compared with the placebo, ruxolitinib had a significant beneficial effect on the proportion of patients that had a reduction in spleen volume of ≥35% at 24 weeks [odds ratio (OR), 109.78; 95% confidence interval (CI), 14.97–804.78] or an increased overall survival rate (OR, 2.02; 95% CI, 0.99–4.12). Ruxolitinib significantly increased the risk of several non-haematological or haematological adverse events, but not the risk of treatment discontinuations (OR, 1.04; 95% CI, 0.50–2.14). Compared with the best available therapy, ruxolitinib had a significant beneficial effect on the proportion of patients that had a reduction in spleen volume of ≥35% at 24 (OR, 68.45; 95% CI, 4.15–1129.19) or 48 weeks (OR, 56.20; 95%CI, 3.40–928.67). Ruxolitinib once again significantly increased the risk of several non-haematological adverse events, serious adverse events and dose reductions or interruptions (OR, 9.60; 95% CI, 4.66–19.81), but not the risk of treatment discontinuations (OR, 1.54; 95% CI, 0.48–4.97). In conclusion, based on the trials included in the present study, the use of ruxolitinib is beneficial in the treatment of MF.